2021
DOI: 10.1007/s10461-021-03241-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Immediate Initiation of Antiretroviral Therapy on Patients' Healthcare Expenditures: A Stepped-Wedge Randomized Trial in Eswatini

Abstract: Immediate initiation of antiretroviral therapy (ART) for all people living with HIV has important health benefits but implications for the economic aspects of patients' lives are still largely unknown. This stepped-wedge cluster-randomized controlled trial aimed to determine the causal impact of immediate ART initiation on patients’ healthcare expenditures in Eswatini. Fourteen healthcare facilities were randomly assigned to transition at one of seven time points from the standard of care (ART eligibility belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…These findings are in slight contrast to a stepped-wedge trial in Eswatini which found that immediate initiation of ART reduced health-care expenditures but had no shortterm improvement on employment. 32,33 Overall, our results suggest that the considerable investments needed to expand access to ART might have significant shortterm and long-term economic returns.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…These findings are in slight contrast to a stepped-wedge trial in Eswatini which found that immediate initiation of ART reduced health-care expenditures but had no shortterm improvement on employment. 32,33 Overall, our results suggest that the considerable investments needed to expand access to ART might have significant shortterm and long-term economic returns.…”
Section: Discussionmentioning
confidence: 75%
“…Our study builds upon the existing literature that has shown large and significant increases in employment and income following ART initiation. [8][9][10]17,18,32,33 However, with the exception of one study that evaluated economic outcomes of people living with HIV and their household members, relatively few of these studies have used a cluster-randomised trial design to evaluate the effects of early ART initiation on socioeconomic outcomes. Our results support the hypothesis that earlier ART initiation can protect employment and other economic indicators for adults and lead to benefits in children's education.…”
Section: Discussionmentioning
confidence: 99%
“…The final sample size was determined by pragmatic aspects such as the availability of a research assistant on a scheduled study day and the travel time to a clinic. Tablet-assisted personal interviews were conducted based on a self-developed questionnaire with new, adapted, and previously used questions [ 30 , 31 ] (Supplement A). The interview included questions about different categories of OOPE, the arrival time at the clinic, travel time to the clinic, forgone earning opportunities, and lost income.…”
Section: Methodsmentioning
confidence: 99%
“…Early HIV diagnosis and prompt treatment are critical for improving HIV treatment outcomes [ 4 ], lowering the cost of medical care [ 5 ], and significantly impacting disease prevention [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%